2019
DOI: 10.29271/jcpsp.2019.04.333
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance versus HbA1c Results as Depictive of Gestational Diabetes Mellitus

Abstract: Objective: To evaluate glucose tolerance patterns in pregnant ladies undergoing 2-hour oral glucose tolerance test (OGTT) for comparing fasting, 1-hour, 2-hour post-glucose load results, HbA1c, sum of all glucose readings with and without gestational diabetes mellitus (GDM) using International Association of the Diabetes and Pregnancy Study Group (IADPSG) diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Comparison of glucose tolerance patterns of pregnant women subjected to 2-H OGTT at fasting, 1-H, 2-H post-glucose load, HbA1c, the sum of all glucose readings among pregnant women with and without GDM using IADPSG criteria shows that the mean PBG at fasting, at 1-hour and 2-hour for both diagnosed and non-diagnosed GDM were; 5.37±1.59 vs. 4.10 ±0.53; 10.67±3.22 vs. 6.71±1.50; and 8.88±3.41 vs. 5.57±1.10 respectively and when adding all these glucose estimation values for diagnosing of GDM produced and ROC with AUC = 0.962 (95% CI: 0.935-0.988) however, AUC for HbA1c = 0.668. The study also reported a high level of HbA1c in subjects with delayed 2-hour post-glucose load peak (Khan 2019) [25].…”
Section: Nambiar (2011) [48]mentioning
confidence: 81%
See 1 more Smart Citation
“…Comparison of glucose tolerance patterns of pregnant women subjected to 2-H OGTT at fasting, 1-H, 2-H post-glucose load, HbA1c, the sum of all glucose readings among pregnant women with and without GDM using IADPSG criteria shows that the mean PBG at fasting, at 1-hour and 2-hour for both diagnosed and non-diagnosed GDM were; 5.37±1.59 vs. 4.10 ±0.53; 10.67±3.22 vs. 6.71±1.50; and 8.88±3.41 vs. 5.57±1.10 respectively and when adding all these glucose estimation values for diagnosing of GDM produced and ROC with AUC = 0.962 (95% CI: 0.935-0.988) however, AUC for HbA1c = 0.668. The study also reported a high level of HbA1c in subjects with delayed 2-hour post-glucose load peak (Khan 2019) [25].…”
Section: Nambiar (2011) [48]mentioning
confidence: 81%
“…Rajput et al, 2012 [24] evaluated the efficacy of HbA1c in combination with OGTT using criteria ADA and IADPSG criteria and reported good sensitivity and specificity at various cut-offs. Similarly, Khan 2019 [25] evaluated glucose tolerance patterns of pregnant women subjected to 2-H OGTT for comparing fasting, 1-H, 2-H post-glucose load results, HbA1c and reported that a combined glucose estimation of these values produced an AUC of 0.962 (95% CI: 0.935-0.988). However, HbA1c as single parameters yields a comparatively low diagnostic accuracy.…”
Section: Gestational Diabetesmentioning
confidence: 99%
“…Another research reported statistical significant rise in fasting insulin and HOM-IR formula (p < 0.05), but no statistical significant difference in fasting blood glucose in cases with SCH compared to healthy controls [20]. Research assessed the IR and glucose levels in subjects with SCH and demonstrated that measures of IR including serum fasting insulin and HOMA-IR rise from euthyroidism to subjects having SCH [21].…”
Section: Discussionmentioning
confidence: 99%
“…After the blood collection, 75g glucose was taken orally, and venous blood collection was conducted again 1 hour post and 2 hours post, respectively. The diagnosis of GDM was made based on the criteria of the International Association of Diabetes and Pregnancy Study Group 30 when any of the following conditions was met: fasting glucose ≥ 5.1 mmol/L (92 mg/dL), or 1-h post glucose ≥ 10.0 mmol/L (180 mg/dL), or 2-h post glucose ≥ 8.5 mmol/L (153 mg/dL).The blood glucose area under the curve (AUC), an effective indicator to reflect the comprehensive level of fasting, 1-h post and 2-h post blood glucose, 31 was also calculated for the participants.…”
Section: Measurement Of Blood Glucose and Diagnosis Of Gdmmentioning
confidence: 99%